Management interventions of pearl millet systems for attaining cereal self-sufficiency in Senegal - Nilson Vieira Junior; Ana Julia Paula Carcedo; Doohong Min; Andre Amakobo Diatta; Alemie Araya; P. V. Vara Prasad; P. V. Vara Prasad; Amadiane Diallo; Ignacio Ciampitti (Frontiers in Sustainable Food Systems, 2024)
Critical management interventions to target the yield potential for each environment are key to food security, increasing the resilience of current agricultural systems in Senegal. Cereal production is highly dependent on pearl millet (Pennisetum glaucum L.) rainfed systems as one of the major field crops for smallholders. This study aims to (i) quantify the production of pearl millet at the department level for the last quinquennial (until 2020), (ii) assess the impact of weather (temperature and precipitation) on the millet-based supply of cereal demand, and (iii) investigate, through crop modeling, the impact of millet-based supply of cereal demand by comparing recommended management interventions with smallholder-based strategies at the department level. Millet-based cereal supply–demand was estimated considering the observed population and the supply via the simulated pearl millet production (obtained using the APSIM-Millet model) at the department level from 1990 to 2021. High temperature and low precipitation occurrence presented a frequency of 35% across departments, leading to a reduction in millet production by roughly 6% relative to the normal average for 32 years. Adoption of recommended management showed the potential to increase the millet supply, more than doubling the current cereal supply, closing the current supply–demand gap (89 kg inhabitant−1). Achieving future cereal self-sufficiency will also require an intensification of other cereal production.